2000
DOI: 10.1074/jbc.m001615200
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific Alternative Splice Mimicry at the Growth Hormone Receptor Locus Revealed by the Lineage of Retroelements during Primate Evolution

Abstract: In humans, growth hormone receptor (GHR) transcripts exist in two isoforms differing by the retention (GHRfl) or exclusion (GHRd3) of exon 3, whereas in mice GHRfl is solely expressed. This species-specific expression pattern is believed to result from an alternative splice event that, on the basis of conflicting data obtained in humans, has been considered to be tissue-, developmentally, and/or individual-specific. To decipher the molecular basis of this unusual trait, we isolated a 6.8-kilobase fragment span… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
182
0
27

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(217 citation statements)
references
References 32 publications
8
182
0
27
Order By: Relevance
“…Most of the primers were designed using Primer 3 26 and others were adapted from previous studies. 21,27,28 Primer sequences can be found in Supplementary Table S1. Amplifications were performed using standard PCR conditions (available upon request).…”
Section: Amplification and Analysis Of The Sequencesmentioning
confidence: 99%
“…Most of the primers were designed using Primer 3 26 and others were adapted from previous studies. 21,27,28 Primer sequences can be found in Supplementary Table S1. Amplifications were performed using standard PCR conditions (available upon request).…”
Section: Amplification and Analysis Of The Sequencesmentioning
confidence: 99%
“…The required dose A polymorphism of the GHR that lacks exon 3 (d3-GHR) during splicing is common in the general population. About half of the population is homozygous for the full-length GHR (fl-GHR), 30-40% is heterozygous for d3-GHR and 10-20% is homozygous for this deletion (7,8,9). It has been reported that the d3-GHR polymorphism shows a comparable distribution between different cohorts of acromegalic patients (6,10,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms of the GHR gene have been reported in the general population and have been described in exons 3, 6 and 10 [31]. While the latter two are classical single nucleotide polymorphisms, the polymorphism in exon 3 is an unusual one, leading to retention (full-length, fl; GHRfl) or deletion of exon 3 (d3; GHRd3), which encodes a 22-amino-acid residue sequence in the extracellular domain [37,38]. GHRd3 has recently been associated with the degree of height increase in response to GH replacement in children born short for gestational age (SGA), in those with ISS, and in a GHD population [39,40].…”
Section: Polymorphism Of the Ghrmentioning
confidence: 99%